2008
DOI: 10.1080/00016480801901774
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VEGF, iNOS, and eNOS is increased in cochlea of diabetic rat

Abstract: Increased cochlear expression of VEGF, iNOS, and eNOS was detected in the diabetic rat. Furthermore, increased permeability of BLB was evidenced by increased cochlear EB extravasation in the diabetic rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
(22 reference statements)
1
16
0
Order By: Relevance
“…Microangiopathy was one of the proposed mechanisms for diabetic patients developing sensorineural hearing impairment. Meanwhile, several literatures have reported the association between microangiopathy and SSHL 35–38. Aimoni et al (2010) described that the risk of getting SSHL tended to increase as the number of cardiovascular risk factors increased 39.…”
Section: Discussionmentioning
confidence: 99%
“…Microangiopathy was one of the proposed mechanisms for diabetic patients developing sensorineural hearing impairment. Meanwhile, several literatures have reported the association between microangiopathy and SSHL 35–38. Aimoni et al (2010) described that the risk of getting SSHL tended to increase as the number of cardiovascular risk factors increased 39.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported a consistent association between microangiopathy and SSHL (3,12,31,32). Aimoni et al (19) stated that the risk of developing SSHL tended to increase with increasing number of cardiovascular risk factors.…”
Section: Microangiopathy As One Of the Mechanismsmentioning
confidence: 96%
“…Medications that enhance microcirculation may benefit diabetic patients confronting the risk of SSHL, especially for diabetic patients of between 50 and 64 years of age and diabetic patients who require triple antidiabetic medication and diabetic patients who have developed new comorbidities of retinopathy and renal disease. Fortunately, with proper and timely management, some previous reports have shown an even better prognosis of SSHL in diabetic patients compared with nondiabetic patients (32).…”
Section: Sshl and Factors That Indicate The Severity Of Diabetesmentioning
confidence: 97%
“…1999). The microvasculature of the cochlea in STZ‐induced diabetic rats also shows a significant increase in VEGF (Liu et al 2008). The reported increases in placental VEGF in the diabetic placenta may well be behind the junctional changes and increased vascular leakage (Babawale et al.…”
Section: Endothelial Adhesion Molecules In Diabetesmentioning
confidence: 99%